Corporate Social Responsibility (CSR) Communication Strategy in an Effort to Form Corporate Image at PT. Resilient Superpower - Shavina, Siti Noer; Andryani, Kristina; Febrianty, Yeni (Asian Journal of Management Analytics, 2025)
To maintain a good corporate image, it is necessary to have strategies and approaches that align with the company's needs and primary goals. On the other hand, effective communication strategies between the company, stakeholders, and the public are also essential in the implementation process of programs to shape the corporate image. One way to achieve this is by implementing Corporate Social Responsibility (CSR) using communication strategies. The communication strategy in a company's Corporate Social Responsibility (CSR) essentially involves planning and management aimed at achieving specific targets in the communication process. Thus, the CSR/PPM programs planned by the company can run smoothly. Therefore, this research is titled "Corporate Social Responsibility (CSR) Communication Strategy in Shaping Corporate Image at PT. Adidaya Tangguh," which aims to explore how the CSR communication strategy shapes the corporate image in a company. This research uses qualitative methods and in-depth interview techniques with data collection techniques including observation, interviews, and documentation. The analysis of this research employs the theory of CSR communication strategies. A good communication strategy in CSR programs is essential for shaping a positive corporate image.